STRATEGIES FOR WATERSHED MANAGEMENT AND PLANNING: A BIBLIOMETRIC ANALYSIS - Engin, Fahrettin; Karadeniz, Enes; Sengün, Mustafa Taner; Sunbul, Fatih (My University, 2024)
In the twentieth century, governance approaches to watershed planning evolved in response to environmental challenges. The paper highlights the importance of watersheds and explores methodologies used in global watershed planning over the last decade, focusing on popular methods and their rationale. Through a systematic literature review of 10,154 publications, using ENDNOTE X9 for citation management (Bramer, 2018), and VOSviewer ver.1.6.18 software (Van Eck and Waltman, 2018) to prioritize publications, the study identified the most cited publications related to \"Watershed\", \"Planning\", and \"Management\". From these, publications aligning with study objectives underwent comprehensive review, totaling 270. Commonly used methods, such as \"Integrated Watershed Management Planning\" and geographic information systems techniques like morphometric indices, overlap weighting, and Analytic Hierarchy Process (AHP), emerged as prevalent findings.
Keywords: Bibliometric analysis; Watershed management and planning; VOS viewer